If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 88 + -1w = 11 Solving 88 + -1w = 11 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-88' to each side of the equation. 88 + -88 + -1w = 11 + -88 Combine like terms: 88 + -88 = 0 0 + -1w = 11 + -88 -1w = 11 + -88 Combine like terms: 11 + -88 = -77 -1w = -77 Divide each side by '-1'. w = 77 Simplifying w = 77
| 7(b+2)=49whatisb | | 18x^2+51x+21=0 | | 42=e-7 | | 9-3k=17-k | | -6-(-9)/3 | | 84/280= | | (2x+4)dx+(3y-1)dy=0 | | 16w=7w+27 | | (2/5x)(5y)(-2x)= | | 2.5-y= | | y=(5-3x)/(7-4x) | | 6-3x-2=-4x | | t-42=24 | | x=(5-3y)/(7-4y) | | 59=k-4 | | 5(a^2)+6a-8=0 | | 4=62-e | | X+11v+4x-v= | | 79-x=1 | | 60-x=41 | | 11+5z=6 | | 4=87-y | | (4y^2)+3y-1=0 | | (5x-9)(9x+8)=0 | | 90-m=1 | | 96-p=63 | | (9k^2)-9k+2=0 | | 26t+5a-4t-2= | | r-28=33 | | 84-v=29 | | (7z^2)-10z+3=0 | | 71-x=22 |